2018
DOI: 10.3389/fgene.2018.00584
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Tuning of Epigenetic Clock

Abstract: Research in the field of gerontology has traditionally focused on later life stages. There is increasing evidence, however, that both the rate of age-related functional decline and the later-life health status can be programmed during early development. The central role of epigenetic mechanisms (methylation of DNA, histone modifications and regulation by non-coding RNAs) in mediating these long-term effects has been elucidated. Both rate and direction of age-associated change of epigenetic patterns (“epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…Alternatively, the different level of DNA methylation in adults versus neonates could be a function of age, analogous to findings in human blood cells, where global DNA methylation increases a function of age until a decrease in late adulthood [46]. This can be a consequence of the epigenetic clock and epigenetic drift [47]. The current findings illustrate the importance of considering both methylation and histone PTM regulation in studies with rapidly developing species such as daphnids.…”
Section: Discussionsupporting
confidence: 58%
“…Alternatively, the different level of DNA methylation in adults versus neonates could be a function of age, analogous to findings in human blood cells, where global DNA methylation increases a function of age until a decrease in late adulthood [46]. This can be a consequence of the epigenetic clock and epigenetic drift [47]. The current findings illustrate the importance of considering both methylation and histone PTM regulation in studies with rapidly developing species such as daphnids.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, however, emerging data suggest that the epigenetic aging “clock” of the placenta may be set largely in early pregnancy and remains largely stable across gestation, lending support to our findings of consistent relationships of PAA with neonatal as well as pre-natal anthropometry measures. For example, PAA has been found to be highly heritable (57%) [41] and the rate of epigenetic aging is found to be developmentally adjusted [36,43] and remains stable across the lifespan [44]. Together, these data suggest that PAA may not exhibit substantial changes across gestation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, twin studies reported considerably high heritability (57%) of epigenetic age acceleration in the placenta [41] as well as other tissues [35,36]. In addition, the rate of epigenetic aging has been found to be developmentally adjusted [36,43] and remains stable across the lifespan [44]. In the present study, we investigated sex-specific associations of PAA with fetal growth, neonatal anthropometry measures, and risk of low birth weight in a cohort of pregnant women in the U.S. with high quality longitudinal fetal sonography data.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation age, evaluated by these predictors, reflects the biological age of a person, which has a close association with individuals’ health status and can be changed by multiple risk factors, such as smoking and obesity (Dugué et al, 2018). Therefore, the difference between DNA methylation age and chronological age (i.e., Δage) may be a promising tool in predicting disease risk and longevity potential in early life (Vaiserman, 2018). Here, we review the dynamics of methylation in aging and discuss the roles of age-dependent methylation changes in the prediction of age and age-related outcomes.…”
Section: Introductionmentioning
confidence: 99%